Rites of passage: Substance dependence and the negotiation of development tasks - a case study - Roux, Catharina (Rhodes University, Faculty of Humanities, Department of Psychology, 1991)
This thesis is an attempt to provide an understanding of drug addiction in its relation to the tasks and arrests which take place during the developmental process. Current theories of drug addiction are situated within the parameters of developmental theory; Object Relations Theory, Lacanian Structuralism and Freud's concept of the Oedipus Complex are drawn on. The dual regressive and progressive function of drugs as it relates to developmental tasks and arrests is illustrated, the argument being that a very specific relationship exists between the compulsive use of drugs and the developmental tasks which need to be avoided as well as those which need to be negotiated. The case study research method is made use of in the attempt to illustrate the links between drug addiction and specific developmental tasks. I present an in-depth analysis of the developmental history of Rafiq Jaffer, an inpatient at the drug unit at Lentegeur Psychiatric Hospital, drawing on the material which was collected during nine months of individual therapy. As Borderline Personality Disorder is the primary diagnosis in the case of Rafiq Jaffer, the emphasis is by necessity put on borderline pathology. The primary aim of the thesis is, however, to highlight the need to understand the compulsive use of drugs within the context of the developmental process, thereby developing a conceptualisation against which further cases may be tested.
Keywords: Drug addiction; Object relations (Psychoanalysis); Psycholinguistics; Oedipus complex; Developmental tasks